Biased information around genetically modified food - Viedma Viedma, Inmaculada; Serrano Megías, Marta; Balanza Galindo, Serafín; López Nicolás, José Manuel (Acta Bioethica, 2015)
Consumer attitudes towards genetically modified food (GMF) are conditioned by the degree of knowledge about them and the information received. The aim of this study is to know the type of information consumers have about GMF and to know whether such information is enough at the time of choosing to consume it or not. The methodology used has been quantitative by descriptive analysis and comparing variables within data. Results obtained show that media is the main source of information, but it only shows a biased view about this type of food. It is urgent to imply all stakeholders to give truthful and complete information, considering all points of view about the topic, with the aim to help the consumer to decide freely about consuming it.